A New Fractional Order Hold and Its Capability in Frequency Response and Zero Placement - Farzad Hashemzadeh; Amin Rezaei Pish-Robat; Parviz Jabehdar-Maralani (Journal of Applied Mathematics)
This paper introduces a new holder with application on digital control systems. This holder is a combination of fractional order hold (FROH) and zero-order hold (ZOH) that has the capability of both holders and a frequency response better than both of ZOH and FROH. For the stability of zeros of the sampled system two theorems are stated and proved with the assumption that the sampling period is very small. Also simulation results are studied to show the effectiveness of the proposed holder and better performance results in comparison with ZOH and FROH.